To find the product of the polynomials \((2x + 1)(x - 4)\), we will use the distributive property (also known as the FOIL method for binomials).
-
Multiply the first terms: \[ 2x \cdot x = 2x^2 \]
-
Multiply the outer terms: \[ 2x \cdot -4 = -8x \]
-
Multiply the inner terms: \[ 1 \cdot x = 1x = x \]
-
Multiply the last terms: \[ 1 \cdot -4 = -4 \]
Now, combine all these results: \[ 2x^2 - 8x + x - 4 \]
Next, combine like terms: \[ 2x^2 - 7x - 4 \]
Thus, the product of the polynomials \((2x + 1)(x - 4)\) is: \[ \boxed{2x^2 - 7x - 4} \]